Economic Aspects of Winter Wheat and Sunflower Production Under Organic Farming Methods - Koch, Krisztina (Acta Agraria Debreceniensis, 2004)
On the basis of data from selected organic crop producing farms around Hortobagy and a significant conventional agricultural enterprise, the efficiency calculation of two important crops, winter wheat and sunflower were compared to each other, according to the organic and the conventional farming methods. The analysis was carried out on the basis of data of the year 2002, helped by the calculation and the comparison of the efficiency indexes. According to the results, the organic winter wheat was more highly profitable in 2002 than the conventional one, and this is because the price ratio of the two was quite high, however the yields and the production costs per hectare were almost on the same level. Considering the sunflower, organic farming was less productive than the conventional one in 2002, as the average yield in the examined organic farms was significantly lower than under the conventional farming method, and this was not compensated by the extra price for the organic crop product.